From a trickle to a torrent : education, migration, and social change in a Himalayan valley of Nepal - Childs, Geoff H., 1963-; Choedup, Namgyal (University of California Press, 2019)
"What happens to a community when the majority of young people move away for education? In Nubri, an ethnic Tibetan enclave in the highlands of Nepal, educational migration (the sending of children to distant institutions for schooling) has become a key component of a family management strategy that is driven by the prospect of social and economic rewards but that entails risk, uncertainty, and unforeseen consequences. The authors draw on ethnographic, demographic, and historical research to document how long-standing religious connections shape contemporary migrations, and how population growth disparities open new schooling opportunities for Buddhist highlanders. They examine parents' motives for sacrificing household labor in favor or sending children to distant schools and monasteries, a trend encapsulated in the oft-repeated phrase "better a pen in hand than a rope across the forehead." The book concludes by investigating dilemmas associated with educational migration, including intergenerational skirmishes over marriage and household succession, threats to the family-based care system for the elderly, and a decline in the level of agricultural production needed to support local religious activities. Better a Pen in Hand chronicles a convergence of demographic and social processes that have led a Himalayan society to the brink of irreversible change."--Provided by publisher.